A generalized expansion method for nonlinear wave equations - Lin, Qun; Wu, Yong Hong; Loxton, Ryan (IOP Publishing, 2009)
A generalized Jacobian/exponential expansion method for finding the exact traveling wave solutions of a nonlinear partial differential equation is discussed. We use this method to construct many new, previously undiscovered exact solutions for the Boussinesq and modified KdV equations. We also apply it to the shallow long wave approximate equations. New solutions are deduced for this system of partial differential equations.